8 (-10x-2)=40
5 (-6x - 9 )=- 20
-2(4x-5)=16 8(4x-2)=13 -6(-3x+2)=21
-9(2x-4)=-5
-6(-4x+1)=10
10(-6x-2)=5
8(-2x-1)=12
-2(-4x+1)=20



Odpowiedź :

Odpowiedź:

Rozwiązanie w załączniku

Zobacz obrazek Nataliawitt33
Zobacz obrazek Nataliawitt33

Odpowiedź:

8 (- 10x - 2) = 40

- 80x - 16 = 40

- 80x = 40 + 16

- 80x = 56  /: (- 80)

x = - 7/10

5 (- 6x - 9) = - 20

- 30x - 45 = - 20

- 30x = - 20 + 45

- 30x = 25  /:(-30)

x = - 5/6

- 2(4x - 5) = 16

- 8x + 10 = 16

- 8x = 16 - 10

- 8x = 6  /: (-8)

x = - 3/4

8 (4x - 2) = 13

32x - 16 = 13

32x = 13 + 16

32x = 29  / : 32

x = 29/32

-6 (- 3x + 2) = 21

18x - 12 = 21

18x = 21 + 12

18x = 33  /: 18

x = 11/6

x = 1 5/6

- 9(2x - 4) = - 5

- 18x + 36 = - 5

- 18x = - 5 - 36

- 18x = - 41  / : (- 18)

x = 41/18

x = 2 5/18

- 6 (-4x + 1) = 10

24x - 6 = 10

24x = 10 + 6

24x = 16  /:24

x = 2/3

10 (- 6x - 2) = 5

- 60x - 20 = 5

- 60x = 5 + 20

- 60x = 25  /: (- 60)

x = - 25/60

x = - 5/12

8 *(- 2x - 1) = 12

- 16x - 8 = 12

- 16x = 12 + 8

- 16x = 20  /: (-16)

 x = - 5/4

 x = - 1 1/4

- 2 * (- 4x + 1) = 20

8x - 2 = 20

8x = 20 + 2

8x = 22  /: 8

 x = 2 6/8

 x = 2 3/4

Szczegółowe wyjaśnienie: